PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF DENGAN METODE MURDER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Setyorini, Ani; Avrilianda, Decky; Widiarti, Nuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of a cooperative learning model using the MURDER method (Mood, Understand, Recall, Detect, Elaborate, Review) in improving elementary school students’ mathematics learning outcomes through a systematic literature review. This study employed the Systematic Literature Review (SLR) method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Article searches were conducted using the Google Scholar, ERIC, Scopus, and SINTA databases, covering the publication period from 2021 to 2026. Of the 487 articles identified, 22 met the inclusion criteria and were analyzed in depth. The results indicate that integrating the MURDER method into cooperative learning models consistently improves elementary school students’ mathematics learning outcomes, with an average increase of 23.7%. Supporting factors for success include structured elaboration stages, fostering a positive mood prior to learning, and student collaboration during the recall and detect phases. The implications of this study provide a theoretical foundation for teachers in implementing MURDER-based cooperative learning at the elementary school level. The implications of this research provide a theoretical foundation for teachers to implement MURDER-based cooperative learning at the elementary school level.